Educação na primeira república parahybana: legislação, imprensa e sujeitos no governo de Camillo de Hollanda (1916-1920) - Biserra, Ingrid Karla Cruz (2015)
This study aimed to analyze the main discussions on education during Camillo de Hollanda government (1916-1920). This required map the involved subjects and analyze the main debates around the sociability network of these. The periodization is justified because in this period there were greater openness in the discussion and effective actions aimed for education in the state of Parahyba, it was possible to observe an intense debate on educational issues, especially on new teaching dictates propounded by the New School ideals that formed and operated up in various school groups created from 1916 in the state. Imbued with the modern principles and guided by the sanitarists ideals, this government has developed a proposal for a state organization based on that ideology, reverberating especially in education legislation. Excelled changes in the capital‟s architecture - opening and enlargement of streets, construction of squares and public buildings, and in the education sector, the reform of Parahybana‟s Primary Education, officiated by Decree 873, of December 21, 1917 as an offshoot of the discussions on the hygienism and the beautification of the city. We used as a source, above all, the official documents - legislation, presidential messages, State' almanac and writings produced by the subjects in newspapers of the period, reports, minutes, correspondence, book and newsletter. In such vehicles, primary and secondary teachers, taken in our research as intellectuals, discussed issues such as school hygiene, physical education, gymnastics, moral and civic education, school medical inspection, among other things immersed in the list of discussions of that period. We observed that, engaged in discussions in terms of ideas, inseparable from the political field, intellectuals created forms of political action to intervene in society. The sociability categories, generation and itinerary, used in our work and extracted from the thought of the French historian, Jean-François Sirinelli, helped us understand the subject in a social and historical perspective and their intellectual trajectories. In general, the elements mentioned in the sources derived from several concerned initiatives to insert the country in modern times under the ideals of health, beauty, progress and civility. Reviewing the intellectual discussions in these areas helps us to understand the complex process of Brazilian education and, in particular, the role played by Paraíba‟s intellectuals in this scenario.